Sketches New and Old, Part 2. - Twain, Mark, 1835-1910 (Salt Lake City, UT : Project Gutenberg, 2004)
"Sketches New and Old, Part 2." by Mark Twain is a collection of short stories published in 1875. This second part continues Twain's anthology of mostly fictional tales, featuring diverse subjects from ghost stories to political satire. The collection includes pieces about frontier life, journalism, science, and society, showcasing Twain's characteristic humor and sharp social commentary. With stories ranging from the supernatural to the absurd, it captures the breadth of Twain's literary range during his early career. (This is an automatically generated summary.)
Answers to correspondents -- To raise poultry -- Experience of the McWilliamses with membranous croup -- My first literary venture -- How the author was sold in Newark -- The office bore -- Johnny Greer -- The facts in the case of the great beef contract -- The case of George Fisher.
Wikipedia page about this book: https://en.wikipedia.org/wiki/Sketches_New_and_Old
Release date is 2004-06-26
Produced by David Widger
Keywords: Humorous stories, American; United States -- Social life and customs -- Fiction